Predicting phosphorus bioavailability from high-ash biochars - Wang, Tao; Camps-Arbestain, Marta; Hedley, Mike; Bishop, Peter (Plant and soil, 2012)
Background and aims Biochars are highly variable in nutrient composition and availability, which are determined by types of feedstock and pyrolysis conditions. The aim of this research was to (a) study the bioavailability of phosphorus (P) in biochars using different feedstocks and pyrolysis conditions; (b) develop a robust chemical method for biochar P availability measurements. Methods In the present study, (a) chemical analysis – including total P and extractable P (2% citric acid, 2% formic acid, and neutral ammonium citrate extraction), and (b) a bioassay test using rye-grass grown in a P deficient sandy soil were used to compare the P bioavailability of different biochars. Biochars were produced from two different feedstocks (dairy manure-wood mixture, MAe; biosolid-wood mixture, BSe) at four different pyrolysis temperatures (250, 350, 450, and 550°C). Results Results showed that P in feedstock was fully recovered in the biochars. After 6 harvests, the biochars were as effective as the P fertilizers tested [Sechura phosphate rocks (SPR) and calcium dihydrogen phosphate (CaP)] in increasing the shoot yield. However, P uptake followed the order of CaP >MAe biochars >BSe biochars >SPR, on a same TP basis. Based on the Mitscherlich equation, 2% formic acid was the most sensitive indicator of P bioavailability in biochars. Conclusions The results suggest that high-ash biochars with high P concentrations are potential P sources with high-agronomic efficiency. We propose the use of 2% formic acid extraction to predict the availability of P in ash-rich biochars.